Daniel el descortes - Fontes, Justine; Jordan, Charles (Nueva York : Children's Press, 2005)
Rude Ralph only learns to be polite after no one will play with him.
Keywords: Behavior -- Juvenile Fiction; Etiquette -- Juvenile Fiction; Spanish language materials